SOCIAL ENTREPRENEURSHIP EDUCATION: INVESTIGATING IMPACTS ON PROBLEM IDENTIFICATION, CREATIVE PROBLEM SOLVING, AND SOCIETAL CHANGE ATTITUDES - Maryam Ibrahim; Suhong Park (Sampoerna University, 2026)
This study investigates the influence of social entrepreneurship education (SEE) on critical entrepreneurial traits among first-year university students. The aim of this study is to examine the impact on empathy, problem-solving abilities, and implementation competence, comprehension of social impact, entrepreneurial attitude, and flexibility. A quantitative approach was employed, analyzing data from participants in a workshop-based SEE program using descriptive and inferential statistics. Findings reveal significant improvements in participants’ ability to identify problems, formulate creative solutions, confidently implement ideas, and engage in social impact initiatives. While participants consistently emphasized sustainability and teamwork, variations were observed in their openness to novel concepts and collaboration in diverse groups. These results underscore the importance of real-world projects, experiential learning, and resilience-building activities within SEE curricula. The study proposes interventions to address skill gaps and align individual motivations with societal objectives, offering specific recommendations for enhancing SEE frameworks to effectively cultivate future leaders of social change.